Interpretation of Sustainability Factor in Wonorejo Mangrove Ecotourism, Surabaya, Indonesia - Rita Parmawati; Anita Qur’ania; Arief Kurnia Riarmanto; Arham Yakub; Agung Sih Kurnianto (Journal of Indonesian Tourism and Development Studies, 2018)
Mangrove Ecotourism Wonorejo Forest (EHMW) is designed by the Surabaya City’s government to have some aspects of nature and education to conservation that may help to save the environment and economy, especially through the tourism. some ecologists revealed that the development of tourism in EHMW runs not balanced and not oriented to the principle of sustainability. This study aims to determine the level of sustainability of EHMW management in Surabaya based on analysis of three sustainability criteria. The study was conducted from September to October 2017. We conducted two methods of data collection: interviews and questionnaires. Assessment is grouped into four levels of sustainability status (%): 0.00-25.00 (unsustainable); 25.01-50.00 (less sustainability); 50.01-75.00 (sufficient sustainability); and 75.01-100,00 (continuous). EHMW management goes into sustainable criteria (77.18%). The value of the sustainability of all criteria is still below 50.1%, or less sustainable. Each criteria’s value was ecology criteria of 29.38%, on the economic criteria of 28.17% and on the social criteria of 19.63%.Key words : Environment, Mangrove, Social, Sustainable, WonorejoMangrove Ecotourism Wonorejo Forest (EHMW) is designed by the Surabaya City’s government to have some aspects of nature and education to conservation that may help to save the environment and economy, especially through the tourism. some ecologists revealed that the development of tourism in EHMW runs not balanced and not oriented to the principle of sustainability. This study aims to determine the level of sustainability of EHMW management in Surabaya based on analysis of three sustainability criterias. The study was conducted from September to October 2017. We conducted two methods of data collection: interviews and questionnaires. Assessment is grouped into four levels of sustainability status (%): 0.00-25.00 (unsustainable); 25.01-50.00 (less sustainability); 50.01-75.00 (sufficient sustainability); and 75.01-100,00 (continuous). EHMW management goes into sustainable criteria (77.18%). The value on the sustainability at all criterias is still below 50.1%, or less sustainable. Each criteria’s value was ecology criteria of 29.38%, on the economic criteria of 28.17% and on the social criteria of 19.63%Keywords: Environment, Mangrove, Social,Sustainable, Wonorejo.